Exploring Stem Cells and Inflammation in Tendon Repair and Regeneration - Vinhas, A. (2018)
Tendon injuries are frequent and are responsible for substantial morbidity both in sports and in the workplace. Despite the endogenous mechanisms of tendon repair and regeneration, tendon healing upon injury is slow and often insufficient to restore complete biomechanics functionality. Inflammation has a pivotal role in tendon healing and failed healing responses contribute to the progression of tendinopathies. However, the molecular and cellular mechanisms involved are poorly understood requiring further insights. During inflammation, bioactive molecules such as cytokines secreted locally at the injury site, influence resident stem cells that contribute as modulatory agents over the niche towards homeostasis, holding great promise as therapeutic agents for tendon pathological conditions associated to unresolved inflammation and failed healing. This review overviews the role of cytokines and resident cells, focusing on the participation of tendon stem cell population in inflammation and tendon healing upon injury and their potential action in resolution of pathological conditions